Immune persistence induced by three doses of 60 μg hepatitis B vaccine in non-responders following standard primary vaccination in Chinese adults - Juan Li; Fanyue Meng; Jingshan Zheng; Qi Liang; Huayu Li; Jingxin Li; Li Zhang; Jianhui Gan; Fengcai Zhu (Taylor & Francis Group, 2021)
This study consisted of two rounds of cross-sectional observations designed to evaluate the persistence of immune protection induced high antigen content hepatitis B (HB) vaccine at 60 μg/1.0 ml formulations administered at a three-dose schedule (Days 0, 28, and 56) in non-responders to routine HB vaccination. In the original phase 3 study, we enrolled 1091 healthy participants (16-60 years old) seronegative for antibody against HB surface antigen (anti-HBs) after primary vaccination. Participants were randomized (2:2:1) to receive three booster doses of HB vaccine containing 60 μg, 30 μg, or 10 μg of antigen per dose 28 days apart. In the group receiving the 60 μg HB vaccine, 428 participants' serum samples were available at pre-vaccination and 28 days after each vaccine dose and were included in immunogenicity analysis. With two written informed consents, we collected blood samples from 276 (67.2%) participants in 2014 and 239 (58.2%) in 2019, who had completed the full course of revaccination and reached the seropositive (anti-HBs≥10 mIU/ml) standard in the 60 μg vaccine group of the original phase 3 study. The HBV seropositive rate was found to decrease from 96.0% in 28 days after receiving the third dose of 60 μg HB vaccine, to 48.2% in 2014, and to 40.6% in 2019, with anti-HBs GMC of seropositive individuals was 584.0 mIU/ml, 142.4 mIU/ml, and 169.1 mIU/ml, respectively. Analysis of 181 vaccinees who had serologic test results available both in 2014 and in 2019, and results revealed a dynamic trend in anti-HBs titer similar to that for the whole immune persistence cohort. Of paramount importance, the serologic test results found that 24.9% (45/181) participants had higher anti-HBs concentrations in 2019 than in 2014, this could be interpreted as natural boosters, secondary to HBV exposure without infection because protected. In conclusion, protective antibody persists about 11 years after immunization of Chinese non-responders with 3 doses of 60 μg HB vaccine. Booster doses of vaccine do not seem necessary to ensure long-term protection.